First report of GI.1aP-GI.2 recombinants of rabbit hemorrhagic disease virus in domestic rabbits in China - Li, Yan; Du, Deyan; Zhou, Long; Su, Liyin; You, Chengcheng; Zhang, Huai; Yu, Jifeng; Xiao, Lu; Huang, Jian (Frontiers in Microbiology, 2023)
The rabbit hemorrhagic disease virus 2 (RHDV2 or GI.2) is a highly contagious agent leading to lethal disease in rabbits. It frequently recombines with other Lagovirus genus, generating epidemical variants with high pathogenicity. In this study, twenty-two liver samples tested positive for GI.2 VP60 gene, were collected in rabbit farms from several geographical regions in China. All GI.2 positive specimens were submitted for RT-PCR detection, nucleotide sequencing and phylogenetic analysis. In addition, suspected GI.2 recombinants were evaluated for virus virulence. The results showed that nine presumptive recombinants were identified by testing for RdRp-VP60 recombination. In these recombinants, four were selected to fully characterize the genome of novel GI.2 recombinant variants, which were described as GI.1aP-GI.2. The nucleotide sequence of these novel variants showed unique recombination pattern and phylogenetic features compared to currently prevalent GI.2 variants. Furthermore, this distinctive recombination of new variant SCNJ-2021 moderately enhanced the virulence of GI.2, even for rabbits vaccinated against parental GI.2. In conclusion, the novel GI.1aP-GI.2 recombinants were identified in rabbit industry in China for the first time, which expanded the knowledge on the phylodynamics and genomic diversity of GI.2 genotype. The rapid molecular evolution and varied pathogenicity of these virus recombinants highlight the urgent need for epidemiological surveillance and for future prevention of these neglected GI.2 variants.